Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1088/0741-3335/52/12/125006
|View full text |Cite
|
Sign up to set email alerts
|

Wall reflection modeling for charge exchange recombination spectroscopy (CXRS) measurements on Textor and ITER

Abstract: Contamination of optical signals by reflections from the tokamak vessel wall is a matter of great concern. For machines such as ITER and future reactors, where the vessel wall will be predominantly metallic, this is potentially a risk factor for quantitative optical emission spectroscopy. This is, in particular, the case when bremsstrahlung continuum radiation from the bulk plasma is used as a common reference light source for the cross-calibration of visible spectroscopy. In this paper the reflected contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…A similar model was used by Banerjee et al with a simplified wall model for modelling spectral diagnostic reflections in Textor and ITER 12 . The Fresnel term, F (n, k), is the analytic solution to Maxwells equations for reflections from a smooth surface [29][30][31] .…”
Section: φ =mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar model was used by Banerjee et al with a simplified wall model for modelling spectral diagnostic reflections in Textor and ITER 12 . The Fresnel term, F (n, k), is the analytic solution to Maxwells equations for reflections from a smooth surface [29][30][31] .…”
Section: φ =mentioning
confidence: 99%
“…Reflection effects are also a major issue with spectroscopic diagnostics on ITER where reflected light could contaminate spectral signals and jeopardise the usefulness of measurements [12][13][14][15][16][17][18] . Some of these studies utilised LightTools 19 , a commercially available ray-tracer, for simulating the magnitude of reflected light and to test possible mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Light reflectance at metallic surfaces is a natural phenomena, which was observed in many kinds of laboratory plasmas, including fusion, Grimm-type, or rf-plasma discharges [35][36][37]. Until now, however, this effect has been associated with the negative role by preventing the accurate derivation of plasma parameters from spectroscopic measurements [38,39]. In this paper, we tried to formulate the plasma conditions at which the light reflectance became so dominant that the emission of atoms could approximate the mirror laboratory with the aim to derive the optical properties of the surface in the absence of additional light sources.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that the influence of stray light would not be negligible also in divertor region [6]. Even for charge exchange recombination spectroscopy, theoretical modeling demonstrated that the stray light issue can be serious in ITER, because the beam attenuation is much greater than that in author's e-mail: kajita.shin@nagoya-u.jp the present devices due to high density and the large device size [7].…”
Section: Introductionmentioning
confidence: 99%